The evaluation of insertion and deletion polymorphism in population and personal identification amidst Chinese populations - Hui Sun; Caiyong Yin; Lei Shang; Chong Wang; Kaiyuan Su; Wanshui Li; Feng Chen; Shilin Li (Wolters Kluwer Medknow Publications, 2018)
For comprehensive understanding of practical application and evaluation on the power of 30 commonly used InDels (Qiagen Investigator DIPplex® kit), we captured population data from 25 Chinese populations and employed F-statistics for population genetics analysis. The results indicated that the distributions of allelic frequencies among populations were in different levels. Furthermore, the phylogeny conforming pairwise FSTdistances showed that the differentiation of majority populations were consistent with their geographic locations and historic dispersals. We conduct the comprehensive correlation analysis between FSTand heterozygosity of 30 InDel loci and provided strong evidence for ongoing InDel loci selection. The FSTvalues of 30 InDels were calculated within 25 Chinese populations, and then, these loci were characterized definitely based on their roles in population genetics or individual identification. Data indicated that 17 InDels with FST<0.01 could be utilized regarding Chinese individual identification (total discrimination power = 0.999985 and cumulative matching probability = 0.00000009). We comprehensively reconstructed the population structure and filled the gap of evaluating the ability of InDels in personal as well as population identification. The application of InDel loci in the forensic area would convincingly promote the development matter of forensic population identification and personal discrimination.